The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12866-015-0485-6
|View full text |Cite
|
Sign up to set email alerts
|

A ferritin-like protein with antioxidant activity in Ureaplasma urealyticum

Abstract: BackgroundUreaplasma urealyticum is a major pathogen associated with many diseases. The ability of U. urealyticum to protect itself from oxidative stress is likely to be important for its pathogenesis and survival, but its oxidative stress tolerance mechanisms remain unclear. This study investigates the antioxidant activity of a ferritin-like protein from U. urealyticum.ResultsThe uuferritin gene, which was up regulated when U. urealyticum was subjected to oxidative stress, was cloned from U. urealyticum and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Free Fe can interfere with the manganese complexes that are used by L. plantarum’s catalase to lower reactive oxygen levels [78]. Thus, the DNA-binding ferritin-like protein could help L. plantarum tolerate the hydrogen peroxide by binding to and storing excess free Fe that would otherwise damage the cell [79]. The second coding sequence encodes a protein that has homology with a low temperature requirement C protein of Listeria monocytogenes , which may be involved in lipid metabolism [80].…”
Section: Resultsmentioning
confidence: 99%
“…Free Fe can interfere with the manganese complexes that are used by L. plantarum’s catalase to lower reactive oxygen levels [78]. Thus, the DNA-binding ferritin-like protein could help L. plantarum tolerate the hydrogen peroxide by binding to and storing excess free Fe that would otherwise damage the cell [79]. The second coding sequence encodes a protein that has homology with a low temperature requirement C protein of Listeria monocytogenes , which may be involved in lipid metabolism [80].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, similar findings demonstrated that M. pneumoniae and M. genitalium encode a homologous protein known as peptide methionine sulfoxide reductase (MsrA), which is an antioxidant repair enzyme that catalyzes the reduction of methionine sulfoxide [Met(O)] residues in proteins to methionine (Dhandayuthapani et al, 2001). In addition, in 2015, our group found that a ferritin-like protein with ferroxidase activity in U. urealyticum could impair harmful oxidative production in vitro (Dai et al, 2015). On the basis of these known data, the mechanism employed by mycoplasma in reaction to oxidative stress plays an important role in mycoplasma survival within host.…”
Section: Overcoming the Immune Effector Molecules Assaultsmentioning
confidence: 99%
“…Free Fe can interfere with the manganese complexes that are used by L. plantarum's catalase to lower reactive oxygen levels [80]. Thus, the DNA-binding ferritin-like protein could help L. plantarum tolerate the hydrogen peroxide by binding to and storing excess free Fe that would otherwise damage the cell [81]. The second coding sequence encodes a protein that has homology with a low temperature requirement C protein of Listeria monocytogenes, which may be involved in lipid metabolism [82].…”
Section: Other Predicted Proteinsmentioning
confidence: 99%